PENERAPAN METODE FLIPPED CLASSROOM TERHADAP PENINGKATAN KEMAMPUAN MENGGUNAKAN WALKER PADA ANAK CEREBRAL PALSY DIPLEGIA DI SLBN CILEUNYI - Putri Hakiki Rizkiani, - (2023)
Cerebral palsy is an individual who has obstacles that are located in the central nervous system so that it has an impact on the movement system. Walking is one aspect of independence that needs to be achieved. However, in practice there are children with diplegic cerebral palsy who have not used assistive devices according to their needs. Therefore, it is necessary to have learning that is implemented in schools when carrying out motion development, namely getting students used to using walker aids. Through the application of the flipped classroom method it is assessed that it can improve the ability to use a walker. This study use an experimental method with a single subject research approach with an A-B-A design and aims to determine the effect of the application of the flipped classroom method on the ability to use walker. The intervention in this study was conducted in 8 sessions. The results of this study indicate that the application of the flipped classroom method is effective in increasing the ability to use a walker. This is evidenced by an increase in the aspect of ability when walking using a walker. Recommedations for the next research is have to develop the flipped classroom method in a different way or by developing a more detailed intervention program about human motor development.